Analysis of Workload and Deciding Workers Optimality at Powder Production Process using NASA-TLX method and KEP/75/M.PAN/7/2004 in PT. XY - Ovi Sadewa; Mochammad Tutuk Safirin; Tranggono Tranggono (OPSI, 2022)
Excessive work fatigue felt by workers due to the addition of working hours or overtime, a less ergonomic work environment is felt by employees who work at PT. XY, workers complained about the large demands of the tasks they received with insufficient rest time, some workers remained focused and concentrated for a long time resulting in physical and psychological workloads on workers. To resolve the problem, a questionnaire was distributed to the entire population of 40 powder production workers using the NASATLX method with a focus on 6 indicators, namely mental needs, physical needs, time requirements, work performance, effort, and frustration levels as well as the KEP/75/M.PAN/7/2004. The purpose of this research is to analyze the workload of powder production workers, determine the dominant indicators based on the NASA-TLX method and determine the optimal number of workers based on KEP/75/M.PAN/7/2004. From this study, the results of the workload of 40 workers were 9 workers in the rather high category, 30 workers in the high category, and 1 worker in the very high category. The number of workers 40 is optimal but the workload is not good enough.